2019
DOI: 10.1177/1350650119877059
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state performance of elliptical contact lubricated with micropolar fluids

Abstract: In this work, the numerical investigation is done for the steady-state performance of elliptical contacts lubricated with micropolar fluids. The Eringen’s micro-continuum theory is applied to deduce the modified Reynolds equation for micropolar fluids. The modified Reynolds equation is discretized by the finite difference technique and evaluated by a multigrid technique for finding the steady-state pressure distribution; simultaneously, the elasticity equation is solved with the multilevel multi-integration me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Zare Mehrjardi et al (2020) concluded that mount angle affects the dynamic performance of lobed bearing to a great extent. Dewangan and Sarangi (2020) worked on the mixing of micro additive particles in lubricant and revealed that it further improves the load capacity of elliptical contact bearing and provides better lubrication performance. Very recently, micropolar lubrication theory was effectively applied by Sharma and Krishna (2020) and Sharma and Krishna (2021) in the investigation of performances for an offset bearing.…”
Section: Introductionmentioning
confidence: 99%
“…Zare Mehrjardi et al (2020) concluded that mount angle affects the dynamic performance of lobed bearing to a great extent. Dewangan and Sarangi (2020) worked on the mixing of micro additive particles in lubricant and revealed that it further improves the load capacity of elliptical contact bearing and provides better lubrication performance. Very recently, micropolar lubrication theory was effectively applied by Sharma and Krishna (2020) and Sharma and Krishna (2021) in the investigation of performances for an offset bearing.…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that the higher eccentricity and micropolarity improve the performance of lobed bearings. Dewangan and Sarangi 17 reported the static performance of elliptical bearings considering a flexible liner. Their study revealed that the load capacity and the life of the bearing can be improved by mixing additives in a lubricant.…”
Section: Introductionmentioning
confidence: 99%